Духовні втрати України в роки Другої світової війни - Щербак, Надія; Shcherbak, N. (Волинський національний університет імені Лесі Українки, 2012)
Висвітлено питання про втрати культурних надбань, яких зазнав український народ в часи ІІ Світової війни. Показано, що війна завдала великої шкоди українській культурі, зокрема бібліотекам та музеям. Проаналізовано політику окупаційної влади щодо українських бібліотечних, музейних та архівних колекцій напередодні та під час війни. The problems of loss of cultural values that have been put to the people of Ukraine duringWorld War II. It is shown that the war inflicted great losses on Ukrainian culture, such aslibraries and museums. We analyze the policy of the occupation authorities against the Ukrainian library, museum and archival collections before and during the war.
Spiritual loss Ukraine During the Second World War
Keywords: культурні цінності; архівні фонди; книжкові колекції; окупаційний режим; нацистська влада; cultural values; archival funds; book collection; the occupation regime; the Nazi government